How can Forensic Linguistics help law enforcement officers? Past, present and future applications - Jiménez Bernal, Miriam (Behavior & Law Journal, 2025)
Forensic Linguistics is a relatively emerging discipline that has established itself as an essential field within Applied Linguistics. Its origin lies in traditional linguistic theories, which provide the necessary tools for the analysis and interpretation of texts and discourses in legal contexts, but also on related fields, such as Literature, where experts have developed methods to attribute the authorship of ancient texts, among others. Over the last decades, Forensic Linguistics has evolved to become a key tool in the resolution of legal cases, from the analysis of witness and expert statements to the identification of perpetrators through language. This article explores the origins of Forensic Linguistics, its development within Applied Linguistics and its relevance in the field of justice. It also discusses some outstanding cases that have demonstrated the impact of this discipline in solving crimes, highlighting how linguistic knowledge can be of great help to law enforcement agencies in identifying patterns, interpreting evidence and clarifying facts. Finally, some of the future trends and challenges are pointed out.